Cystic Interstitial Lung Diseases: A Pictorial Review and a Practical Guide for the Radiologist - Aquilina, Giulia (Diagnostics (Basel), 2020)
A cyst is a round circumscribed area of low attenuation, surrounded by epithelial or fibrous wall. Cysts can frequently occur on chest computed tomography (CT) and high-resolution computed tomography (HRCT); multiple parenchymal cysts of the lungs are the most typical feature of cystic lung interstitial diseases, characterizing a wide spectrum of diseases—ranging from isolated lung disorders up to diffuse pulmonary diseases. The aim of this review is to analyze scientific literature about cystic lung interstitial diseases and to provide a practical guide for radiologists, focusing on the main morphological features of pulmonary cysts: size, shape, borders, wall, location, and distribution. These features are shown on free-hand drawings and related to HRCT images, in order to help radiologists pursue the correct differential diagnosis between similar conditions.